Nuclear-lipid-droplet proteome: carboxylesterase as a nuclear lipase involved in lipid-droplet homeostasis - Lucía C. Lagrutta (Heliyon, 2021)
Nuclear-lipid droplets (nLD)—a dynamic cellular organelle that stores neutral lipids, within the nucleus of eukaryotic cells—consists of a hydrophobic triacylglycerol –cholesterol-ester core enriched in oleic acid (OA) surrounded by a monolayer of polar lipids, cholesterol, and proteins. nLD are probably involved in nuclear-lipid homeostasis serving as an endonuclear buffer that provides or incorporates lipids and proteins participating in signaling pathways, as transcription factors and enzymes of lipid metabolism and nuclear processes. In the present work, we analyzed the nLD proteome and hypothesized that nLD-monolayer proteins could be involved in processes similar as the ones occurring in the cLD including lipid metabolism and other cellular functions. We evaluated the rat-liver–nLD proteome under physiological and nonpathological conditions by GeLC-MS2. Since isolated nLD are highly diluted, a protein-concentrating isolation protocol was designed. Thirty-five proteins were identified within the functional categories: cytoskeleton and structural, transcription and translation, histones, protein-folding and posttranslational modification, cellular proliferation and/or cancer, lipid metabolism, and transport. Purified nLD contained an enzyme from the lipid-metabolism pathway, carboxylesterase 1d (Ces1d/Ces3). Nuclear Carboxylesterase localization was confirmed by Western blotting. By in-silico analyses rat Ces1d/Ces3 secondary and tertiary structure predicted would be equivalent to human CES1. These results—the first nLD proteome—demonstrate that a tandem-GeLC-MS2-analysis protocol facilitates studies like these on rat-liver nuclei. A diversity of cellular-protein function was identified indicating the direct or indirect nLD participation and involving Ces1d/Ces3 in the LD-population homeostasis.